Prolonged Grief Disorder and Early Onset Depression in Children - Basuki, ⁠Shinta Maulydiyah; Prisnidiawati, Ajeng; Karida, Rika Nur; Rasyid, Rezza Dwi Ar; Ridlo, Fairuz; Ilahi, Marintik; Algristian, Hafid (Medicor : Journal of Health Informatics and Health Policy, 2025)
Children who experience the death of a significant attachment figure, such as a parent or grandparent, are particularly vulnerable to Prolonged Grief Disorder (PGD) and early-onset depression. Unlike adults, children may manifest grief through somatic symptoms, irritability, or behavioral disturbances rather than overt sadness. The grief process in childhood, if not properly addressed, can disrupt emotional regulation, cognitive development, and psychosocial functioning. This case report discusses a 10-year-old boy who developed depressive symptoms following the loss of his grandfather, with whom he had a strong emotional bond. His symptoms included persistent sadness, social withdrawal, emotional dysregulation, and somatic complaints. These were compounded by environmental stressors such as parental divorce, an emotionally invalidating caregiving environment, and exposure to an aggressive alcoholic family member. Assessment involved clinical interviews, psychiatric evaluations, and a comprehensive review of literature addressing grief and child mental health. The patient met the diagnostic criteria for PGD and showed comorbid early-onset depression, highlighting the interconnected nature of grief and affective disorders in children. Neurobiological factors, particularly dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis, were considered in the etiology. The case underscores the importance of early recognition, family-centered psychosocial interventions, and integrative therapeutic approaches including cognitive-behavioral therapy (CBT), expressive arts, and complementary methods such as aromatherapy. This report emphasizes the urgent need for culturally sensitive, trauma-informed strategies to help bereaved children navigate loss and prevent chronic psychiatric outcomes. Early intervention plays a critical role in promoting resilience and long-term mental well-being in grieving children.